श्रीबसवप्पशास्त्री - Nagarjarao, H.V. (Karnataka Samskrit University Bangalore, 2013)
This is a Biography in Sanskrit of Shri Basavappashastry.
Basavappashastry
Keywords: श्रीबसवप्पशास्त्री; Basavappashastry; Biography; Sanskrit; Sanskrit